1991
DOI: 10.1007/bf00572881
|View full text |Cite
|
Sign up to set email alerts
|

Results of partial patellectomy

Abstract: We present an assessment of 200 patellar fractures treated mostly (175) by partial patellectomy. In 23 cases in which the quadriceps mechanism was 75% intact (MRC power approximately 4), the fractures were treated conservatively, with an overall acceptable result. The operative series with an average follow-up of 3 years has shown 80.3% excellent to good results. A classification of fractures of the patella, based on the anatomical fracture line and quadriceps functional loss as recorded in 690 case histories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…However, in clinical studies where the results of partial patellectomy were reported, incidences of extensive patellar tendon ossification were not detected [9,10]. Saltzman et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical studies where the results of partial patellectomy were reported, incidences of extensive patellar tendon ossification were not detected [9,10]. Saltzman et al .…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the fracture of the patella consists of one main proximal fragment and a severely comminuted lower pole of the patella. In this condition sufficient reduction and stable fixation is unlikely to be achieved and partial patellectomy has to be considered [ 67 ]. However, partial resection of the lower pole reduces the distance between the patella and tibial tuberosity and can lead to a patella baja with increased patellofemoral contact pressures leading to higher rates of anterior knee pain as well as an early onset of osteoarthritis [ 45 ].…”
Section: Operative Treatmentmentioning
confidence: 99%
“…With patellar fractures in human patients, where internal fixation has been performed but imperfect fracture reduction was achieved, knee function will deteriorate over time and thus where anatomic reconstruction of the patella is not possible, partial patellectomy is a viable alternative (Pandey and others 1991). This leads to a good to excellent outcome in over 75% of cases (Saltzman and others 1990, Pandey and others 1991).…”
Section: Discussionmentioning
confidence: 99%
“…With patellar fractures in human patients, where internal fixation has been performed but imperfect fracture reduction was achieved, knee function will deteriorate over time and thus where anatomic reconstruction of the patella is not possible, partial patellectomy is a viable alternative (Pandey and others 1991). This leads to a good to excellent outcome in over 75% of cases (Saltzman and others 1990, Pandey and others 1991). In long‐term follow‐up of human patients after partial patellectomy, mean active range of motion was 94%, the circumference of the thigh was 100% and the strength of the quadriceps was 85% of these measurements in the contralateral extremity (Saltzman and others 1990).…”
Section: Discussionmentioning
confidence: 99%